2016
DOI: 10.1007/s12272-016-0850-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors for cancer treatment

Abstract: During immune responses antigen-specific T cells are regulated by several mechanisms, including through inhibitory receptors and regulatory T cells, to avoid excessive or persistent immune responses. These regulatory mechanisms, which are called 'immune checkpoints', suppress T cell responses, particularly in patients with chronic viral infections and cancer where viral antigens or tumor antigens persist for a long time and contribute to T cell exhaustion. Among these regulatory mechanisms, cytotoxic T lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 94 publications
0
36
0
1
Order By: Relevance
“…It has two ligands, PD-L1 and PD-L2. PD-L1 is broadly expressed[42]. Several studies have already demonstrated that PD-L1 or PD-1 is highly expressed on tumor cells in gastric cancer patients[43-46].…”
Section: Tils In Gastric Cancermentioning
confidence: 99%
“…It has two ligands, PD-L1 and PD-L2. PD-L1 is broadly expressed[42]. Several studies have already demonstrated that PD-L1 or PD-1 is highly expressed on tumor cells in gastric cancer patients[43-46].…”
Section: Tils In Gastric Cancermentioning
confidence: 99%
“…19,20 CTLA-4 acts as a coinhibitory receptor of the CD28-B7 axis, which has a critical role in T-cell response and in cancer escape of tumor surveillance; blocking this pathway prevents induction of tolerance and increases activated T-cell number and repertoire. 18,19,21 Anti-CTLA-4 ipilimumab was the first immuno-oncology therapy to show overall survival (OS) benefit in metastatic melanoma compared with the standard of care, 10,22 and in 2011 ipilimumab initiated the rise of checkpoint inhibitors as cancer therapy ( Figure 1). Anti-PD-1 biologics, such as nivolumab and pembrolizumab, block PD-1 signaling on T cells, and the PD-L1 inhibitors atezolizumab, avelumab, and durvalumab block PD-L1 on tumor cells and/or tumor-infiltrating immune cells; both methods inhibit the interaction between PD-1 and PD-L1 and/or PD-L2 and release the PD-1/PD-L1 immune pathway.…”
mentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Tumors escape immune surveillance in the host body by various methods, including upregulation of suppressor immune cells, coinhibitory receptor-ligand expression, and production of immunosuppressive cytokines. 18 CTLA-4 and PD-1/PD-L1 have complementary and synergistic roles in regulating T-cell activation ( Figure 2). 19,20 CTLA-4 acts as a coinhibitory receptor of the CD28-B7 axis, which has a critical role in T-cell response and in cancer escape of tumor surveillance; blocking this pathway prevents induction of tolerance and increases activated T-cell number and repertoire.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective of these immunotherapies to date have been immune checkpoint inhibitors (ICIS), such as ipilimumab, nivolumab and pembrolizumab 22,23 .…”
Section: Principles Of Combining Radiation Therapy With Immunotherapymentioning
confidence: 99%